2021
DOI: 10.26577/iam.2021.v2.i2.06
|View full text |Cite
|
Sign up to set email alerts
|

Community Understanding, Perception and Practices on Infection Prevention From the Coronavirus Disease (Covid-19): A Qualitative Study in Rural Bangladesh

Abstract: The current study had tried to assess the rural community's understanding, perception and practices on infection prevention to protect from the COVID-19 pandemic.It is a qualitative study using eight focus group discussions (FGDs) and 40 in-depth interviews (IDIs). Manual content analysis processes were used.The respondents had good understanding of COVID-19 but had limited knowledge of its spreading, symptom and prevention. Community health workers and adolescents were found to be more aware of COVID-19 issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Such experiences are likely to create a continuing barrier to accessing comprehensive healthcare [ 31 , 36 ]. Other studies indicated these shortcomings in the provision of care were caused by challenges in traveling to and from workplaces and no assistance provided to reach health facilities [ 33 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such experiences are likely to create a continuing barrier to accessing comprehensive healthcare [ 31 , 36 ]. Other studies indicated these shortcomings in the provision of care were caused by challenges in traveling to and from workplaces and no assistance provided to reach health facilities [ 33 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies conducted in Bangladesh explored social and community perceptions regarding the prevention and control of coronavirus. One such study in rural Bangladesh revealed a lack of comprehensive knowledge about the spread, symptoms, and prevention of the virus (19). Additionally, there existed a disparity between community beliefs concerning the pandemic and the sciencedriven interventions advocated by health professionals (20).…”
Section: Introductionmentioning
confidence: 99%